Impact of Landuse Morphology on Urban Transportation - Okeke, Francis O.; Gyoh, Louis; Echendu, Ifeanyi F. (Civil Engineering Journal, 2021)
People, cities, nations and the world, in general, would remain largely underdeveloped without transportation systems. However, Transportation puts significant pressure on land use and poses a great challenge to urban sustainability in developing countries. This study examines the influence of Land use structure on Intra-urban transportation in the developing city of cities in the West African sub-region â€“ using Enugu city as a case study. The study uses a descriptive research method. A survey was carried out in six districts within the Enugu metropolis based on a stratified, purposive sampling technique. Questionnaires were used as data collection instruments; 400 respondence participated in the study employing Yamane equation. Furthermore, a twelve-hour (7 am to 7 pm) traffic count was conducted to assess traffic volume. The study finding revealed that Transportation within the urban areas is significantly impacted by Land-use structure, city morphology, neighbourhood characteristics in terms of population and residential density of the city. The hypothesis suggests no significant difference between the various land uses across the Enugu metropolis (p = 0.129). It was also discovered that an average of 122,431 Passenger Car Units (PCU) constantly ply the metropolis roads to service a total population of 564,725 daily, indicated a high rate of car dependency. The study surmises that land use generates vehicular traffic, which impacts the socio-economic environment and the effectiveness of the transportation system. The significance of this study is that the findings contribute to the existing knowledge base that would advance stratic policy formation towards acceleration of the uptake of sustainable urban transportation systems in the region.Â Doi: 10.28991/cej-2021-03091758 Full Text: PDF